2017
DOI: 10.1161/hypertensionaha.117.09516
|View full text |Cite
|
Sign up to set email alerts
|

Office Pulse Pressure Is a Predictor of Favorable Outcome in Young- to Middle-Aged Subjects With Stage 1 Hypertension

Abstract: (Adriano Mazzer). The online-only Data Supplement is available with this article at http://hyper.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
3
12
2
7
Order By: Relevance
“…However, the clinical significance of pulse pressure in younger patients remains controversial. A recent study has suggested that office pulse pressure is a negative predictor of MACE in young patients with hypertension [30]. Although the present study found that high pulse pressure was associated with an increased risk of MACE and that there was no significant interaction between the cardiac treatment strategy and age in patients with pulse pressure b 60 mmHg and those with pulse pressure ≥ 60 mmHg, further investigations are needed to assess whether these results are observed in younger patients.…”
Section: Discussioncontrasting
confidence: 67%
“…However, the clinical significance of pulse pressure in younger patients remains controversial. A recent study has suggested that office pulse pressure is a negative predictor of MACE in young patients with hypertension [30]. Although the present study found that high pulse pressure was associated with an increased risk of MACE and that there was no significant interaction between the cardiac treatment strategy and age in patients with pulse pressure b 60 mmHg and those with pulse pressure ≥ 60 mmHg, further investigations are needed to assess whether these results are observed in younger patients.…”
Section: Discussioncontrasting
confidence: 67%
“…Similarly, the HELIUS study found a U‐shaped association between brachial/central SBP and age for subjects aged <40 years old 12 . The J‐shaped association between age and ISH prevalence has been reported in prior studies 12,25,31 . For example, the NHANES 1999–2004 that male aged 30–39 years old had a lower ISH prevalence rate than those male aged 18–29 years old (1.94% vs. 2.48%) 25 .…”
Section: Discussionsupporting
confidence: 53%
“…Die Prognose ist dementsprechend gut und eine blutdrucksenkende Therapie ist den Leitlinien entsprechend nicht erforderlich [14,18,19]. Im Gegensatz zur ISH im Alter gilt: je höher die Blutdruckamplitude bei den Jungen, umso besser ist die Prognose [20].…”
Section: Juvenile Isolierte Systolische Hypertonieunclassified